Study on the anti-free radical, antibacterial, and whitening effects of sea buckthorn extract and its product development - Ao She; Yating Li; Litian Jiang; Ruochen Liang; Siyuan Hao; Kaize Li; Yan Zhou (Journal of Dermatologic Science and Cosmetic Technology, 2025)
Background: Seabuckthorn is a widely distributed, high-yielding shrub valued for its medicinal and nutritional properties, with its fruit rich in flavonoids and polysaccharides. While studies have focused on the anti-inflammatory, antioxidant, anticancer, and immune-boosting effects of these compounds, research on their skincare benefits is limited. Additionally, there is a lack of method development and characterization of their actual skincare efficacy. Objective: The main objective of this study was to investigate the antimicrobial, whitening, moisturizing, and restorative effects of seabuckthorn polysaccharides and flavonoids. An innovative gel leave-on mask was developed with these active ingredients, and its stability and skincare efficacy were evaluated through characterization experiments focusing on antibacterial, whitening, moisturizing, and restorative effects. Materials and Methods: Seabuckthorn polysaccharides and flavonoids were extracted using both aqueous and alcoholic methods. The antibacterial, antioxidant and whitening efficacy of sea buckthorn flavonoids was investigated by the antibacterial test of Propionibacterium acnes, ABTS free radical scavenging test and tyrosinase inhibition test. An innovative gel leave-on mask formula was developed, incorporating glycerol glucoside and hydrolyzed collagen for added moisturizing and reparative benefits. The stability of the gel mask was tested for pH stability, ionic strength stability, and thermodynamic stability using measurements of particle size, polydispersity index (PDI), and zeta potential. Finally, the practical efficacy of the gel leave-on mask was evaluated through participant trials, measuring skin parameters such as vascular density, skin roughness, moisture content, and pigmentation. Results: The study demonstrated that seabuckthorn flavonoids exhibited excellent antimicrobial, anti-inflammatory and whitening effects. The gel leave-on mask formulation proved stable. Participants showed significant improvements in skin parameters, including reduced roughness, increased moisture content, and enhanced pigmentation balance, confirming the practical efficacy of the product. Conclusion: In conclusion, this study fills the gap in the systematic verification of the multifaceted skincare benefits of seabuckthorn flavonoids and polysaccharides, while also developing a product that efficiently integrates these two active ingredients. The formulation's practical efficacy was confirmed, showing significant effects in antibacterial, anti-inflammatory, and whitening applications.